Quartet cards as the media of career exploration for lower-grade primary school students - Yulia Ayriza; Farida Agus Setiawati; Agus Triyanto; Nanang Erma Gunawan; Moh Khoerul Anwar; Nugraheni Dwi Budiarti (Program Pascasarjana Universitas Negeri Yogyakarta & HEPI, 2017)
A career developed through the optimization of one’s potentials will irrevocably play a role in the development of self-identity as well as the psychological well-being of the individual. When children are introduced and allowed to explore as many career options as possible during their developmental stage, they are more likely to have a fruitful career development in the future. The preceding study showed that the career interests and knowledge of lower-grade primary students fit the Holland Career Categories: realistic, investigative, artistic, social, enterprising, and conventional (RIASEC). It was also found that the students’ career interest and knowledge levels varied, with most in the low level. This second-year study aims to expand the results of the previous study by developing the use of Quartet cards as the media of career exploration for lower-grade primary students. By using the research and development method, this study develops Quartet Career Cards into three difficulty levels: low, medium, and high. The Quartet cards media have undergone feasibility tests conducted by experts in theory and media, as well as a series of field testing consisting of preliminary, main, and operational stages among a total of 266 primary students of grades 1, 2, and 3. A revision was made on several components including the images, information, colors, font sizes, illustration styles, and card sizes. The findings show that Quartet Career Cards meet the feasibility standards for the media of career exploration